Northern Sea Route development plan until 2035 as an instrument of state innovation policy - A. Yu. Smirnov (Вестник университета)
The Northern Sea Route is a promising transport project. Its effective development requires the use of various innovative technologies. The purpose of the study is to determine the role and significance of the Northern Sea Route development plan until 2035, adopted by the Government of the Russian Federation in August 2022, as an instrument of the state’s innovation policy. After analyzing the content of the activities presented in the plan, the author comes to the conclusion that, despite some shortcomings (the inclusion of activities already underway, measures to develop railway infrastructure that are not related to the Northern Sea Route, arithmetic errors that are usually not typical for documents of this level) the practical implementation of the proposals presented in the plan for the development of a nuclear icebreaker fleet, the creation of an Arctic satellite constellation, the formation of an environmental monitoring system is impossible without the active introduction of innovations, fundamental and applied research in the field of natural, technical, medical and social sciences. This allows us to consider the plan as an instrument of the innovation policy of the federal executive authorities for the development of the country’s national economy in the long term.